2019
DOI: 10.1093/ajcn/nqy383
|View full text |Cite
|
Sign up to set email alerts
|

Portion size has sustained effects over 5 days in preschool children: a randomized trial

Abstract: Background Although short-term studies have found that serving larger portions of food increases intake in preschool children, it is unknown whether this portion size effect persists over a longer period or whether energy intake is moderated through self-regulation. Objectives We tested whether the portion size effect is sustained in preschool children across 5 consecutive days, a period thought to be sufficient for regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 53 publications
5
37
0
Order By: Relevance
“…This leads to lower sensory satisfaction and high caloric intake (Cecil, Francis, & Read, 1999;Haber, Heaton, Murphy, & Burroughs, 1977;Smethers & Rolls, 2018;Viskaal-van Dongen, Kok, & de Graaf, 2011;Zijlstra, Mars, de Wijk, Westerterp-Plantenga, & de Graaf, 2008). Unfortunately, it has also been demonstrated that when people, both adults and kids, ingest a larger portion version of a meal or snack (intake increase of about 140-200 cal), they do not compensate for this in later meals, resulting in a higher daily average caloric intake (Forde, 2018;Rolls, Laster, & Summerfelt, 1989;Smethers et al, 2019). This effect was found to be more pronounced in those with lower satiety responsiveness, as determined by a validated questionnaire.…”
mentioning
confidence: 99%
“…This leads to lower sensory satisfaction and high caloric intake (Cecil, Francis, & Read, 1999;Haber, Heaton, Murphy, & Burroughs, 1977;Smethers & Rolls, 2018;Viskaal-van Dongen, Kok, & de Graaf, 2011;Zijlstra, Mars, de Wijk, Westerterp-Plantenga, & de Graaf, 2008). Unfortunately, it has also been demonstrated that when people, both adults and kids, ingest a larger portion version of a meal or snack (intake increase of about 140-200 cal), they do not compensate for this in later meals, resulting in a higher daily average caloric intake (Forde, 2018;Rolls, Laster, & Summerfelt, 1989;Smethers et al, 2019). This effect was found to be more pronounced in those with lower satiety responsiveness, as determined by a validated questionnaire.…”
mentioning
confidence: 99%
“…This suggests that some children are more sensitive to the portion size served and confirms the findings of Smethers et al . () that poor satiety responsiveness predicts greater intake when large portions are served.…”
Section: Downsizing Meal Itemsmentioning
confidence: 97%
“…Of particular interest was the observation that individual differences were important in the response to the PSE, with bodyweight status and eating traits (lower satiety responsiveness and higher food responsiveness) predicting greater susceptibility to the PSE (Smethers et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Evidence shows that young children consume larger amounts of the manipulated foods, without a compensatory decrease in the intake of other foods, leading to greater energy intake during a single meal 8 . This effect has been shown to be sustained over several days 9 . Studies have also shown that increasing portion sizes of healthier foods such as milk and fruit alongside other foods results in increased consumption of these foods, without increasing total energy intake (kcal) of the meal 10, 11 .…”
Section: Introductionmentioning
confidence: 99%